PENGARUH KOMBINASI MASSASE DAN COUNTER PRESSURE TERHADAP NYERI PERSALINAN KALA I DI WILAYAH KABUPATEN CILACAP - Lina Puspitasari; Fatimah Azzahroh (Jurnal Inovasi Daerah, 2022)
Labor pain is a problem that cannot be overcome until now. Almost all pregnant women experience labor pain. This can result in stress, smooth muscles tighten and blood vessels narrow, uterine contractions decrease and oxygen supply decreases, and uterine ischemia occurs. Counter pressure massage techniques are often used to overcome these problems. However, this technique has not been combined with lumbar massage. So there is a need for further research on this technique. The research design is qualitative with a case study research strategy. The research subjects taken were 3 informants at BPM "N". The research data was taken using observation and direct observation techniques and set forth in the documentation of Varney's care. Then the data is tabulated using domain analysis. The results of this study indicate that there are benefits of massage and counter pressure techniques for active phase I labor pain. The results obtained from the three respondents had the highest score before the intervention was carried out, namely 7. The average pain scale after the action was carried out decreased by 2 points. The conclusion of this study is that massage techniques and counter pressure have a significant effect on the first stage of labor pain.